Risk Factors for Hemorrhagic Stroke among Adults in the Democratic Republic of the Congo: A Hospital-Based Study in a Limited Resource Setting. (7th November 2022) - Musung, Jacques Mbaz; Kakoma, Placide Kambola; Bugeme, Marcellin; Banze, Jeef Paul Munkemena; Mukeng, Clarence Kaut; Muyumba, Orly Ngungwa; Kamalo, Berthe Mwad; Kapya, Harvey Kabulo; Ngongo, Ghyslain Lambo; Kitwa, Laurent; Yav, Evariste Tshibind; Mukuku, Olivier; et al.
Abstract : Background . The prevalence of stroke is increasing in sub-Saharan Africa. The scarcity of hospital-based stroke data in Lubumbashi (in the Democratic Republic of the Congo) led to the study, which was designed to describe the epidemiology of stroke and identify risk factors associated with hemorrhagic stroke among adult patients in Lubumbashi. Methods . This was a cross-sectional study of 158 adult patients admitted for stroke in the internal medicine department of Lubumbashi University Clinics from January 2018 to December 2020. Sociodemographic and clinical features, cardiovascular risk factors, and hospital mortality were collected. A logistic regression has determined the risk of developing a hemorrhagic stroke. Results . Of 9, 919 hospitalized patients, 158 had a stroke with a hospital prevalence of 1.6%; 86 (54.4%) patients had a hemorrhagic stroke while 72 (45.6%) had an ischemic stroke. Of which 41.1% (65/158) were women. The mean age was 60.8 ± 13.3 years. Main clinical signs were hemiplegia (63.3%), headache (48.7%), speech disorders (38.6%), and dizziness (38.6%). Hypertension (82.9%) and hyperglycemia (53.2%) were the most common risk factors. Inhospital mortality was 22.8%. After logistic regression, independent predictors for developing hemorrhagic stroke were hypertension (aOR = 8.19 ; 95% CI: 2.72–24.66; p < 0.0001 ) and atrial fibrillation (aOR = 4.89 ; 95% CI: 1.41–16.89; p = 0.012 ). Conclusion . This study highlights the high stroke mortality in a resource-limited hospital and the burden of hypertension in the development of hemorrhagic stroke. It illustrates the need to establish stroke care setting to improve the quality of stroke care.